Coronary Atherosclerotic Phenotype and Plaque Healing in Patients with Recurrent Acute Coronary Syndromes Compared with Patients with Long-term Clinical Stability: An in Vivo Optical Coherence Tomography Study - Vergallo, Rocco; Porto, Italo; Annibali, Gianmarco; Galli, Mattia; Migliaro, Stefano; Fracassi, Francesco; Aurigemma, Cristina; Leone, Antonio Maria; Buffon, Antonino; Burzotta, Francesco; Trani, Carlo; Niccoli, Giampaolo; et al. (JAMA Cardiology, 2019)
Importance: At one end of the coronary artery disease (CAD) spectrum, there are patients with multiple recurrent acute coronary syndromes (rACS), and at the other end there are those with long-standing clinical stability. Predicting the natural history of these patients is challenging because unstable plaques often heal without resulting in ACS. Objective: To assess in vivo the coronary atherosclerotic phenotype as well as the prevalence and characteristics of healed coronary plaques by optical coherence tomography (OCT) imaging in patients at the extremes of the CAD spectrum. Design, Setting, and Participants: This is an observational, single-center cohort study with prospective clinical follow-up. From a total of 823 consecutive patients enrolled in OCT Registry of the Fondazione Policlinico A. Gemelli-IRCCS, Rome, Italy, from March 2009 to February 2016, 105 patients were included in the following groups: (1) patients with rACS, defined as history of at least 3 acute myocardial infarctions (AMIs) or at least 4 ACS with at least 1 AMI; (2) patients with long-standing stable angina pectoris (ls-SAP), defined as a minimum 3-year history of stable angina; and (3) patients with a single unheralded AMI followed by a minimum 3-year period of clinical stability (sAMI). Data were analyzed from January to August 2018. Exposures: Intracoronary OCT imaging of nonculprit coronary segments. Main Outcomes and Measures: Coronary plaque features and the prevalence of healed coronary plaques in nonculprit segments as assessed by intracoronary OCT imaging. Results: Of 105 patients, 85 were men (81.0%); the median (interquartile range) age was 68 (63-75) years. Median (interquartile range) time of clinical stability was 9 (5.0-15.0) years in the ls-SAP group and 8 (4.5-14.5) years in the sAMI group. Patients in the rACS and sAMI groups showed similar prevalence of lipid-rich plaque and thin-cap fibroatheroma, which was significantly higher than in those with ls-SAP (lipid-rich plaque 80.0% [n = 24 of 30] vs 76.3% [n = 29 of 38] ...